2019
DOI: 10.3389/fvets.2019.00174
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Monitoring of Antimicrobial Consumption in Vietnamese Small-Scale Chicken Farms Highlights Discrepancies Between Study Metrics

Abstract: Chicken is, among farmed species, the target of the highest levels of antimicrobial use (AMU). There are considerable knowledge gaps on how and when antimicrobials are used in commercial small-scale chicken farms. These shortcomings arise from cross-sectional study designs and poor record keeping practiced by many such farmers. Furthermore, there is a large diversity of AMU metrics, and it is not clear how these metrics relate to each other. We performed a longitudinal study on a cohort of small-scale chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 13 publications
10
70
1
Order By: Relevance
“…For pigs, chickens, and aquaculture (all aquatic species combined) data on AMU were obtained from quantitative published surveys [13][14][15][16]. Data on on AMU through consumption of commercial feed (i.e.…”
Section: Main Textmentioning
confidence: 99%
“…For pigs, chickens, and aquaculture (all aquatic species combined) data on AMU were obtained from quantitative published surveys [13][14][15][16]. Data on on AMU through consumption of commercial feed (i.e.…”
Section: Main Textmentioning
confidence: 99%
“…It has been shown that antimicrobials intended for veterinary use are extremely affordable in the region (average of 0.56 cents of a USD per kilogram treated) and represent only a small fraction of overall chicken production costs [12]. We found that, despite high levels of AMU by chicken flocks in the area [15], antimicrobial sales represented a relatively small fraction of the total income of veterinary drug shops. There were, however, the large difference across establishments.…”
Section: Discussionmentioning
confidence: 66%
“…High levels of AMU have been reported both in chicken and pig production in the Mekong Delta of Vietnam [13][14][15]. This behaviour is partly driven by the prevailing farming conditions that lead to a high incidence of disease and mortality [8].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, the quantity of antimicrobials used in chicken production is estimated at 138.0 doses/1,000 animal‐days [inter quartile range (IQR) 91.1–438.3], a higher amount than AMU in the two other major terrestrial food animal species (pig and cattle) (Cuong, Padungtod, Thwaites, & Carrique‐Mas, ). Previous studies have reported exceptionally high levels of antimicrobial use (AMU) in chicken farms in the Mekong Delta region of Vietnam (Carrique‐Mas et al., ; Carrique‐Mas et al., ; Cuong et al., ; Nguyen et al., ). However, there are currently no published data on the quality of antimicrobial products used in these farming systems.…”
Section: Introductionmentioning
confidence: 99%
“…TA B L E 1 Characteristics of 20 antimicrobial products investigated, sorted by the number of flocks where they were used 91.1-438.3], a higher amount than AMU in the two other major terrestrial food animal species (pig and cattle) (Cuong, Padungtod, Thwaites, & Carrique-Mas, 2019). Previous studies have reported exceptionally high levels of antimicrobial use (AMU) in chicken farms in the Mekong Delta region of Vietnam (Carrique-Mas et al, 2015;Carrique-Mas et al, 2019;Cuong et al, 2019;Nguyen et al, 2016).…”
mentioning
confidence: 99%